Sosialisasi Inovasi Minuman: Teh Kulit Kopi untuk Gaya Hidup Sehat di Desa Tleter Kecamatan Kaloran Kabupaten Temanggung - Anindi Putri Safira Wulandari; Mazida Nurmania Rizki; Fredy Hermanto; Haryono Haryono (Jurnal Bina Desa, 2026)
Coffee husk waste in Tleter Village, Temanggung Regency is usually only used for fertilizer, animal feed, and sometimes thrown away immediately. Processing coffee skins into nutritious tea drinks is an innovation and a new step in processing coffee skin waste. The method in this article is counseling or socialization. This outreach activity consists of several stages, namely presentation, discussion and presentation of product samples. The aim of this outreach is to provide education regarding the use of coffee husk waste into products that are good for health. The result of this activity is understanding and information about the benefits of coffee skin served in tea form for body health. The discussions held showed the enthusiasm and interest of PKK women in developing cascara tea as a new product, which has great potential to increase their income. Presenting product samples allowed participants to experience cascara tea directly and understand the importance of attractive packaging.